Quelle sorte d’entité matérielle est une œuvre d’art ? - Yaël Kreplak (Images Re-Vues)
In this paper I consider artworks’ materiality not as a historical, methodological or theoretical issue (a research problem) but as a practical problem, faced by museum professionals, who, in their everyday business with artworks, have to negotiate, determine and redefine the material properties of the objects they are in charge of. Drawing on materials collected through an ethnography of conservation practices at the contemporary department at the French National Museum of Modern Art (MNAM - Centre Pompidou), and focusing on the management of a particular artwork from the collection, Le Magasin de Ben, I wish to address the question “what kind of material entity is an artwork” as a practical, situated and circumstantial matter, so as to demonstrate the multiplicity of perspectives and practices through which artworks are defined, experienced and constituted in the museum.